Prácticas musicales e identidades en Salta. Reelaboraciones y sentidos en torno al folklore - Irene López (Les Cahiers ALHIM)
Simon Frith argues that popular music makes up one of the cultural expressions with the greatest efficiency in the construction of identities, as it allows to describe "the social in the individual and the individual in the social, the mind in the body and the body in the mind" (2003). Adopting this perspective we wonder about the role of massively disseminated popular music in local contexts of production and the strategies at stake, both concerning its musical as literary and interpretative aspects. For that purpose, we undertake the study of two productions located in Salta in the first quarter of the 21st Century, one of them, Saltalogía by the jazz composer Daniel Tinte (Salta, 1969) edited in 2005; the other, El canto hereje, a CD produced as a tribute from rock to the folklore musician of Salta Gustavo "Cuchi" Leguizamón (1917-2000), edited in 2014. In these productions, we are interested in analyzing the ways of construction of subjectivity and the manners of space representation considering the many dialogs, tensions and appropriations between various traditions and styles; specially, the reinterpretations and senses around the folklor.